Factors Influencing Landowner Support for Stewardship in the Carolinian Life Zone - Knight, Mark (University of Waterloo, 2007)
Stewardship is a key tool for the protection of natural areas at the landscape-scale. This is nowhere more evident than in the Carolinian Life Zone of Southern Ontario, where habitat exists for approximately 80% of Canada’s Species at Risk and where the majority of land is in private ownership. However, the implementation of stewardship initiatives has not always been successful. While an outcome of stewardship has been increased protection, initiatives that do not serve landowner needs can lead to reduced landowner support for future stewardship efforts. As such there is a need to look beyond landowner participation/non-participation, and instead examine the factors influencing landowner support for stewardship. The existing stewardship research on landowner support has found three main influencing factors: stewardship ethics, property rights concerns and bureaucracy. To examine if these themes are relevant to the Carolinian Life Zone interviews were conducted at three case study sites: Point Pelee, Rondeau and Long Point. The findings indicate that while the three broad themes are present, certain themes are more salient than others. It was also found that the local stewardship context made a great difference for landowner responses. Recommendations from the findings involve changes to stewardship programs, the role of landowners in conservation decision-making and land-use regulations.
Keywords: Stewardship; Protected Areas; Geography